2017
DOI: 10.1007/s00382-017-3918-0
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of transient-eddy and inter-member variabilities in global and regional climate model simulations

Abstract: associated with natural phenomena of weather disturbances and IV is a model feature contributing to the uncertainties of simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In Leduc et al (2019) the authors state that "In the case of a climate system under transient forcing, the use of [IMV equation] to assess temporal variability using the inter-member spread involves weaker assumptions than calculating the residual temporal variability from detrended time series." (Leduc et al, 2019, p. 681), based on the study by Nikiéma et al (2018). A recent publication by Wang et al (2019) even concludes that the IMV of winter sea level pressure over Eurasia in a SMILE is driven by the same mechanisms as observed IAV via an EOF analysis.…”
Section: Projected Changes In Internal Variability and The Connectionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Leduc et al (2019) the authors state that "In the case of a climate system under transient forcing, the use of [IMV equation] to assess temporal variability using the inter-member spread involves weaker assumptions than calculating the residual temporal variability from detrended time series." (Leduc et al, 2019, p. 681), based on the study by Nikiéma et al (2018). A recent publication by Wang et al (2019) even concludes that the IMV of winter sea level pressure over Eurasia in a SMILE is driven by the same mechanisms as observed IAV via an EOF analysis.…”
Section: Projected Changes In Internal Variability and The Connectionmentioning
confidence: 95%
“…Using IMV is an elegant way to get around this challenge. Some recent publications support the concept of using IMV as an approximation of IAV, although the two have different background meanings: while IAV has a physical meaning and represents the variability of a consecutive sequence of weather phenomena, IMV is a measure of variability without a direct physical meaning (Nikiéma et al, 2018).…”
Section: Projected Changes In Internal Variability and The Connectionmentioning
confidence: 99%
“…where N is the ensemble size (N = 50), X it the monthly mean temperature over the given time period for member i and year t, andX ot the ensemble mean (average over all members) at year t. Assuming ergodicity between temporal and inter-member variances (Nikiéma et al 2017), σ a,b…”
Section: Projected Changes In Temperature Interannual Variabilitymentioning
confidence: 99%
“…There is also evidence, as highlighted in reviews by Westra et al (2014) and Madsen et al (2014), that anthropogenic climate change is also likely leading to an increase in recorded subdaily precipitation extremes. For instance, studies showed increases for durations ranging from multiple hours to days for North America (Brommer et al 2007;Burn et al 2011;Kunkel et al 2013;Muschinski and Katz 2013) and for Europe (Arnone et al 2013;Leahy and Kiely 2011;Madsen et al 2009;Ntegeka and Willems 2008;Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%